The Role of Teacher Administration in Supporting the Effectiveness of Learning Activities at Islamic Boarding Schools - Atikah; Fina Kholij Zukhrufin (Jurnal Pendidikan Nusantara, 2026)
This study aims to analyze the influence of teacher administration on the effectiveness of teaching and learning activities at Nashrus Sunnah Islamic Boarding School Madiun, describe the implementation of teacher administration in the field, and identify institutional efforts to improve its quality. This study employed a descriptive qualitative approach with data collected through in-depth interviews, observation, and documentation. Data validity was ensured through source and methodological triangulation, while data analysis followed the Miles and Huberman model consisting of data reduction, data presentation, and conclusion drawing. The findings reveal that teacher administration encompassing lesson plans, teaching journals, assessment rubrics, and learning documentation has a significant positive influence on the effectiveness of KBM, particularly in enhancing teaching readiness, the regularity of the learning process, student participation, and the clarity of learning indicators and evaluation. However, implementation remains suboptimal, as 10–15% of teachers still submit documents late, administrative formats are inconsistent, and dual-role burdens hinder reporting consistency, especially at the Wustha and Ulya levels. This study concludes that synergy between institutional policies and the real needs of teachers in the field is essential to realize effective, efficient, and sustainable teacher administration in the context of pesantren education, and recommends continuous mentoring, simplification of administrative formats, and dedicated time allocation for administrative tasks.